KOMODIFIKASI AGAMA DALAM PERSPEKTIF SOSIOLOGI EKONOMI; (STUDI KASUS HAJI FURODA) - Rety Reka Merlins; Hartatia Nur; Sitti Nurhayati (Halu Oleo University, 2025)
This study aims to examine and analyse the phenomenon of religious commodification from the perspective of economic sociology, focusing on the case of Hajj Furoda as a form of commercialised worship practice. Religious commodification refers to the process by which religious symbols and rituals—including the pilgrimage to Mecca—are treated as marketable commodities within a capitalist system. A qualitative descriptive method was employed through literature review, drawing on various sources such as academic journals, books, government regulations, and media reports related to the implementation and controversy surrounding Hajj Furoda in Indonesia. The findings reveal that Hajj Furoda reflects a shift in the meaning of pilgrimage, from a spiritual obligation to a premium product within the religious industry. This phenomenon generates ambivalence in society: on the one hand, it is seen as a practical solution for fulfilling the fifth pillar of Islam more quickly; on the other hand, it raises concerns about unequal access, the commercialisation of religious teachings, and potential regulatory violations. From the perspective of economic sociology, the Hajj Furoda case illustrates a complex relationship between religion, the market, and the state—where spirituality is increasingly shaped by the logic of profit and social status. This study underscores the importance of ethical scrutiny and regulatory oversight of religious practices that have been absorbed into capitalist systems.